A COMPARATIVE STUDY ON THE WAGE RATE PAID - BALWANT KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
The report titled "Time for Equality at Work" (ILO 2003a) stresses the ongoing wage discrimination between employment of equivalent value, indicates the harmful repercussions of such discrimination, and restates the urgent need to take the required actions to remove said discrimination. In a study that was published not too long ago (2006), the European Commission laments the fact that the wage gap between men and women continues to be unacceptably large and shows no indications of narrowing. These results should also be of concern to governments and social partners in a great number of nations located both to the South and to the North. It would seem that the ineffectiveness of pay equality law and, more specifically, the inability of companies to comply with it are to blame for the persistence of pay discrimination.